2012
DOI: 10.1371/journal.pone.0033732
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Type I and III Interferon Signalling Pathways Occurs in Lung Epithelial Cells Infected with Low Pathogenic Avian Influenza Viruses

Abstract: The host response to the low pathogenic avian influenza (LPAI) H5N2, H5N3 and H9N2 viruses were examined in A549, MDCK, and CEF cells using a systems-based approach. The H5N2 and H5N3 viruses replicated efficiently in A549 and MDCK cells, while the H9N2 virus replicated least efficiently in these cell types. However, all LPAI viruses exhibited similar and higher replication efficiencies in CEF cells. A comparison of the host responses of these viruses and the H1N1/WSN virus and low passage pH1N1 clinical isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 68 publications
7
60
1
Order By: Relevance
“…However, the underlying molecular mechanisms often remain obscure. In accordance with our study, virus-specific differences in host cell signaling, including differential JNK activation, have recently been observed (44). Moreover, NS1 proteins of two avian IAVs differentially inhibit the doublestranded-RNA-induced activation of the AP1 promoter (45).…”
Section: Discussionsupporting
confidence: 91%
“…However, the underlying molecular mechanisms often remain obscure. In accordance with our study, virus-specific differences in host cell signaling, including differential JNK activation, have recently been observed (44). Moreover, NS1 proteins of two avian IAVs differentially inhibit the doublestranded-RNA-induced activation of the AP1 promoter (45).…”
Section: Discussionsupporting
confidence: 91%
“…Unlike in MDCK cells, the replication capa- bilities of codon-deoptimized influenza viruses were altered in human A549 cells (compare Fig. 4A and 5A), perhaps due to signaling pathways in human A549 cells that are different from those in MDCK cells or absent in MDCK cells (59,60). For instance, since NS1 is an IFN-I antagonist protein, the differences in replication rates observed could correspond with species-specific IFN-I production or be correlated with IFN-I-stimulated gene (ISG) expression (20,21,54).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate if the influenza viruses carrying codon-deoptimized NS showed different replication kinetics in a cell line that more accurately represents the cells targeted in a natural human infection, A549 human lung epithelial cells were used (59,60). To that end, human A549 cells were infected with WT NS or codondeoptimized NS viruses (MOI, 0.001), and at 12, 24, 48, and 72 h postinfection, viral titers were evaluated (Fig.…”
Section: Codon Deoptimization Of Pr8 Virus Nsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, conducted in China and elsewhere, suggested that Grampositive bacterial and fungal infections could cause a mild increase in IL-6 levels (Lehrnbecher et al, 1999), whereas viral infection could cause an increase in IFN-γ (Sutejo et al, 2012), but not in IL-6 or IL-10 levels (Engervall et al, 1995). Therefore, in this study, the high increases of IL-6 and IL-10 levels [>10 times (means ± SD)] in infected children could be considered to indicate Gram-negative bacterial infection.…”
Section: Discussionmentioning
confidence: 98%